2015
DOI: 10.1007/s11095-015-1660-z
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Targeted Theranostic Nanoemulsion for Image-Guided Ovarian Cancer Therapy

Abstract: Purpose Platinum-based therapies are the first line treatments for most types of cancer including ovarian cancer. However, their use is associated with dose-limiting toxicities and resistance. We report initial translational studies of a theranostic nanoemulsion loaded with a cisplatin derivative, myrisplatin and pro-apoptotic agent, C6-ceramide. Methods The surface of the nanoemulsion is annotated with an endothelial growth factor receptor (EGFR) binding peptide to improve targeting ability and gadolinium t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 39 publications
(53 reference statements)
3
33
0
3
Order By: Relevance
“…However, the difference was statistically significant only in the A549-DDP model. These results confirm the influence of EGFR-peptide targeted nanoparticles to target the cancer cells, which is in agreement with previous studies from our group where the same peptide was successfully used [40,65,66].…”
Section: Evaluation Of the Tumor Targeting Efficiencysupporting
confidence: 92%
“…However, the difference was statistically significant only in the A549-DDP model. These results confirm the influence of EGFR-peptide targeted nanoparticles to target the cancer cells, which is in agreement with previous studies from our group where the same peptide was successfully used [40,65,66].…”
Section: Evaluation Of the Tumor Targeting Efficiencysupporting
confidence: 92%
“…We have developed a highly flexible stable oil in water nanoemulsion (NE) platform that fits all the required attributes for the clinical development of a theranostic approach suitable for treating ovarian cancer patients. [3][4][5] Using this NE platform, we designed and created stable NMI-500, a folate (FA) targeted theranostic that has the capacity to: carry a lethal payload of docetaxel (DTX); overcome ATP-binding cassette (ABC) gene family mediated drug efflux; [6][7][8][9][10][11] specifically interact with folate receptor-a (FR-a) which is commonly expressed on ovarian tumor cells; 11,12 and act as an MRI contrast agent so DTX pharmacodynamics and disease burden can be tracked by a non-invasive, clinically relevant imaging modality (Fig. S1).…”
Section: Introductionmentioning
confidence: 99%
“…S1). 4,5,13 FR-a is one of three isoforms of the folate receptor: a, b, & g. FR-a is a 38 kD glycosyl-phosphatidylinositolanchored glycoprotein that binds FA with a K d <1 nM, »10fold more affinity than the reduced form of FA and is highly expressed in a number of human cancers including ovarian, lung, breast, renal cell carcinoma, brain, and head & neck cancers. 14 FR-a mediates FA uptake through endocytosis, showing very high affinity but low capacity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a drug carrier, they have several advantages such as effective encapsulation, sustained drug release and long circulatory times. It is suggested that if targeting moieties such as folate (Patlolla & Vobalaboina 2008), thiamine , endothelial growth factor receptor (EGFR) binding peptide (Ganta et al 2015), mannose (Rutishauser & Gutknecht 1976), etc., to be anchored to the nano-emulsion, they can deliver their cargo with significantly higher efficiencies and remain longer at the disease site to allow for total transfer of the drug molecules. The size of nano-emulsions is <500 nm in diameter; these can successfully incorporate poorly soluble drugs (Ganta et al 2008;Vyas et al 2008).…”
Section: Nano-emulsionsmentioning
confidence: 99%